Avaliação do desgaste a campo de modelos de pontas de pulverização - Luiz Augusto Mateus Santos (2022)
The defensive application techniques must be carried out correctly to ensure satisfactory and safe results, through their rational use. From this perspective, the question remains whether producers are respecting the recommendation to change spray nozzles when there has been wear on the nozzles in the order of 5 to 10% in relation to the increase in flow? Thus, the objective of this work was to evaluate the effects of wear on some models of hydraulic spray nozzles in relation to the flow and on the characteristics of the population of drops generated after their replacement by the rural producer in the central region of the State of Mato Grosso do Sul . Eight treatments (point models) were used, originating from three properties located in the central region of the State of Mato Grosso do Sul. The tips were collected during the replacement period for new parts, meeting the criteria of each property. The eight evaluated nozzles were: JA3_a, AD_D 11002, BD 11002, JCI 80025, AXI 11003, CVI 110025 and AVI 11002. The nominal flow of the spray nozzles was measured, following the ISO 10625 standardization norms. , volumetric median diameter, relative amplitude, and percentage of drops smaller than 100 µm. Initially, the correlations between the evaluated variables were estimated, in addition to the analysis of canonical variables to verify the similarity between the variables and each evaluated tip. The nozzle models used were replaced late because they had an average flow greater than 5% of the reference value. The BD02 tip model was the one that presented the highest values for use, flow rate and percentage of drops smaller than 100 µm, indicating that its replacement should have been carried out at an earlier time.